2013
DOI: 10.1007/s00216-013-6873-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective fluorescence response and magnetic separation probe for 2,4,6-trinitrotoluene based on iron oxide magnetic nanoparticles

Abstract: Despite the rapid development of nanomaterials and nanotechnology, it is still desirable to develop novel nanoparticle-based techniques which are cost-effective, timesaving, and environment-friendly, and with ease of operation and procedural simplicity, for assay of target analytes. In the work discussed in this paper, the dye fluorescein isothiocyanate (FITC) was conjugated to 1,6-hexanediamine (HDA)-capped iron oxide magnetic nanoparticles (FITC-HDA Fe3O4 MNPs), and the product was characterized. HDA ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…3 displays the optical absorption spectra of S1, S2 and their combination at a 1 : 1 ratio. The superposition of the spectra of S1 and S2 comes to a curve, which is very close to the observed one 15,50,51,63 in band locations and shapes. The two bands at 447 nm and 506 nm are in accordance with the observed ones 15,50 at about 465 nm and 515 nm.…”
Section: Optical Absorptionsupporting
confidence: 73%
See 1 more Smart Citation
“…3 displays the optical absorption spectra of S1, S2 and their combination at a 1 : 1 ratio. The superposition of the spectra of S1 and S2 comes to a curve, which is very close to the observed one 15,50,51,63 in band locations and shapes. The two bands at 447 nm and 506 nm are in accordance with the observed ones 15,50 at about 465 nm and 515 nm.…”
Section: Optical Absorptionsupporting
confidence: 73%
“…As IR and Raman spectra had been used to characterize the existence of either the Meisenheimer complex or TNT anion in a TNT-amino-QD solution, 26,43,51,63 we computed the vibrational spectra with IR and Raman intensities of S1 and S2 at the M06-2X/6-311++G(d,p) level and compared them with the measurements. Fig.…”
Section: Raman Spectramentioning
confidence: 99%
“…4.1.3 Other small organic fluorophores. Besides the above discussed small organic fluorophores, some other new small fluorophores have also been reported in explosive detection such as quinoline, 146,147 fluorescein, 148 rhodamine, 149 squaraine dye, 47 For example, Xu's group employed the ICT mechanism and found that DNSA-SQ could sense picric acid sensitively and selectively via a fluorescence turn-on signal in the near-infrared region (Fig. 11A).…”
Section: Small Molecule Fluorophores For Explosive Detectionmentioning
confidence: 99%
“…Because of the three nitro groups in the TNT molecule, the aromatic ring of TNT is severely electron-deficient, it interacts readily with electron-rich molecules to form a complex. Other analogs of TNT with less nitro groups on the aromatic ring have much weaker interaction [45]. The proposed method exhibited good selectivity and reliability as supported by the standard addition in real samples, which is described in the following section.…”
Section: Interferencesmentioning
confidence: 79%